Phenomics as an approach to Comparative Developmental Physiology - McCoy, Jamie C. S.; Spicer, John I.; Ibbini, Ziad; Tills, Oliver (Frontiers in Physiology, 2023)
The dynamic nature of developing organisms and how they function presents both opportunity and challenge to researchers, with significant advances in understanding possible by adopting innovative approaches to their empirical study. The information content of the phenotype during organismal development is arguably greater than at any other life stage, incorporating change at a broad range of temporal, spatial and functional scales and is of broad relevance to a plethora of research questions. Yet, effectively measuring organismal development, and the ontogeny of physiological regulations and functions, and their responses to the environment, remains a significant challenge.'Phenomics', a global approach to the acquisition of phenotypic data at the scale of the whole organism, is uniquely suited as an approach. In this perspective, we explore the synergies between phenomics and animal development, with a focus on developmental physiology, a key factor in consideration of sensitivity to drivers of global change. We then identify how organismal development itself provides an excellent model for pushing the boundaries of phenomics, given its inherent complexity, the comparably smaller size of developing organisms, taxonomic diversity, and the applicability of embryonic development to a broad suite of research questions. Collection, analysis and interpretation of whole organismal phenotypic data are the largest obstacle to capitalising on phenomics for advancing our understanding of biological systems. We suggest that phenomics within the context of developing organismal form and function could provide an effective scaffold for addressing grand challenges in both developmental biology and phenomics.